Initial Experience With Robotic Pancreatic Surgery: Technical Feasibility and Oncological Implications. Issue 1 (February 2016) - Coratti, Andrea; Di Marino, Michele; Coratti, Francesco; Baldoni, Giulia; Guerra, Francesco; Amore Bonapasta, Stefano; Bencini, Lapo; Farsi, Marco; Annecchiarico, Mario
Abstract : Robotic surgery has been introduced in the field of minimally invasive surgery to improve the handling of high-demanding procedures with encouraging results. We aimed to evaluate the clinical safety and the oncological adequacy of robot-assisted pancreatic surgery by analyzing a consecutive series in terms of surgical and oncological outcomes. A total of 53 consecutive cases including 36 pancreatoduodenectomies (PD) and 14 distal pancreatectomies (DP) were evaluated. The overall postoperative morbidity and mortality were 32% and 3.8%, respectively. Radical resection was achieved in 93.7% of PD and 100% of DP, with a mean number of harvested lymph nodes of 29.8 for PD and 20.5 for DP. The 3-year cumulative overall survival was 44.2% and 73.9% for patient with pancreatic ductal adenocarcinoma and nonductal malignancy, respectively. Robotic technology may be useful to reproduce conventional open pancreatic surgery with a minimally invasive approach, overcoming some of the intrinsic limitations of conventional laparoscopy.